Object's RGB color extraction - Iqbal Zulkarnain, Abdul Aziz (2007)
Color Blindness, or Color Vision Deficiency, is an eye condition where a person is not able to distinguish certain colors or shades of colors to some degree. As we know, color blind people facing problems that related to color recognizing in their daily life. Due to this problem, the purpose of this project is to help color blind people to recognize the object color around them to make their life better by extracting RGB color in the image. This project is focusing on software development. The color image that need to be recognize will be captured by a camera and processed using MATLAB Image Processing Toolbox software that have been programmed. The method for analyzing the image consist of RGB color pixel statistic to check the major color in the image and RGB color extraction for color definition that used in result display as color reference. The result will be displayed on monitor screen by wording in popup message box.